A model to identify the factors of supplier communication and financial availability to support the lean manufacturing implementation in small and medium scale enterprises. (2018) - Ramadas, T.; Satish, K.P.; Mathew, K. Aibel
The aim of the research paper is to present the factors associated with supplier communication and financial availability that constitute a successful implementation of lean manufacturing within the small and medium scale enterprises. Structural equation modelling (SEM) was employed to test the model drawing on a sample of 124 small and medium scale enterprises (SMEs) Kerala India. Specification search in Amos 20 was employed to find out the best theoretical model given an initial model using the following fit function criteria, Chi-square, Chi-square-df (C-df), Akaike information criteria (AIC), Browne-Cudeck criterion (BCC), Bayes information criterion (BIC), chi-square divided by the degrees of freedom and significance level. Communication with supplier and financial availability with 16 elements were considered in the questionnaire. Specification search was carried out build up the model on the collected data which identified two factors with 12 key variables.